Reimagining Masculinity through Shifts in Male Identity in Contemporary Popular Culture - Cinta, Cinta; Putri, Alya; Tenriani, Andi (Journal Social Humanity Perspective, 2025)
This qualitative research paper explores the masculinity rebranding in the current popular culture, that is, how the phenomenon of masculine identities in the contemporary society is being challenged by hybrid-emotional and intersectional representations. Through exposure to media texts, social media posts, and semi-structured interviews of the youth, the study aims to identify the level to which traditional hegemonic masculinity still exists where other forms of masculinity gain more visibility. The results suggest that popular culture is becoming more reflective of men as able to express emotion, flexible in their aesthetic expression, and able to portray multiple identities, which may be undermining strict ideas of gender roles. Nevertheless, the ideals of hegemonic masculinity are still strong, especially in the genres of action movies, sports press, and gaming subcultures, which are rooted in the primordial social and company concept of being tough, dominant, and stoic. The paper highlights how the cultural industries and digital platforms can control as well as commodify masculinity where identity changes are packaged to suit consumer tastes and market rationales. These changes have far reached repercussions in the area of management and organizational research with implications especially in the field of leadership, diversity and workplace culture. Relational and inclusive models of leadership can be found in emotional openness, hybridity, and intersectional masculinities, whereas structural constraints of the persistence of hegemonic masculinity remain in the workplace to determine norms and authority. This study adds to the body of gender theory and management literature by conceptualizing masculinity as a cultural and managerial project, and highlighting the fact that continuity and change in male identities are a negotiation. The paper provides feedback on the ways that modern organizations and media producers can relate to shifting masculinities to create more inclusive and dynamic practices.